Structure of near-surface magnetic layer in iron borate - Zubov, V.E.; Strugatsky, M.B.; Skibinsky, K.M. (Functional Materials, 2007)
Magnetic structure of inhomogeneously magnetized near-surface magnetic layer for non-basal baces of FeBO₃ single crystals has been calculated. That layer has macroscopic thickness and can be observed in easy-plane weak ferromagnets. The calculation in based on our theory of Iron Borate surface magnetism.